The behavioural economics of competitive balance: Implications for league policy and championship management - Oliver Budzinski; Tim Pawlowski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2014)
The theory of competitive balance represents one of the core concepts of sports economics. Based upon an international research project analyzing the perception of competitive balance by consumers (Pawlowski 2013a, 2013b; Pawlowski & Budzinski 2013, 2014), we argue in this paper that behavioural explanations of competitive balance may offer additional insights for selected sports economics and, in particular, sports policy problems, complementing the standard view on competitive balance. After summarizing the standard analysis of competitive balance in sports economics concerning theory, policy and empirical record in chapter 2, we report the main theoretical and empirical insights from our research project (chapter 3, closely drawing on the respective publications). In addition to providing a more comprehensive picture of the behavioural economics of competitive balance, we add a discussion of sports policy implications (chapter 4). While perceived competitive balance is found to matter, there are rather narrow conditions for sports policy interventions or restrictive regulations of competition by the league management (or sports associations). Furthermore, it is not the balance of the overall league that matters. Instead, it is sufficient or even advantageous if the most relevant subcompetitions, like the race for the championship or the fight against relegation, are 'balanced' among a narrow oligopoly of contenders.
Keywords: D12; L83; 330; sports economics; sports policy; sports management; competitive balance; behavioural economics; competitive balance defense